DEVELOPMENT OF SUSTAINABLE INTERACTIONS OF RUSSIAN ORGANIZATIONS IN MODERN CONDITIONS - I. Rumyantseva (Вестник университета)
The article considers tendencies of development of interactions of organizations that arise in modern conditions. Currently, the prevailing types of interaction determine the General conditions for activities in an economy. Therefore, the trends in the development of interactions are extremely important to manage the successful operation of any organization. In the changing due to the economic crises conditions, which include dramatically increasing the uncertainty of the environment and a General slowdown, a tendency, consisting in the increased interest of companies to move from rigid competitive relations to the balance relations of cooperation and competition has identified, as well as few other important trends. The use of the identified trends in governance processes will contribute to the success of organizations and the overall development of the economy.